2009
DOI: 10.1111/j.1467-8543.2009.00736.x
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of Workplace Representatives, Union Power and Democracy in Australia

Abstract: The purpose of this article is to illuminate the views and experiences of workplace representatives in Australia in the context of falling union density, and to analyse factors that are most strongly associated with subjective union power at the workplace level, as perceived by delegates. The analysis relies on a large random survey of workplace delegates in eight significant Australian unions. The article describes the situation broadly facing delegates as shown by the survey and analyses a set of factors ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
1
5

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(49 citation statements)
references
References 26 publications
3
39
1
5
Order By: Relevance
“…Gender issues were identified by some male delegates as a reason to have both male and female delegates working in a team. Confirming earlier quantitative research (Peetz and Pocock, 2009), little formal training in networking was reported. Delegates asked for more opportunities to meet and share experiences in networks organised by the union, including both formal and regular networking sessions.…”
Section: Barriers and Facilitators Of Networksupporting
confidence: 81%
See 1 more Smart Citation
“…Gender issues were identified by some male delegates as a reason to have both male and female delegates working in a team. Confirming earlier quantitative research (Peetz and Pocock, 2009), little formal training in networking was reported. Delegates asked for more opportunities to meet and share experiences in networks organised by the union, including both formal and regular networking sessions.…”
Section: Barriers and Facilitators Of Networksupporting
confidence: 81%
“…Unions' embeddedness in networks (Lévesque and Murray, 2010) and delegates' involvement in networks (Peetz and Pocock, 2009) are accepted as being an important source of union power. Yet the development of delegates' networks may be the role at which unions are weakest (Peetz and Pocock, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…A first aspect of deliberative vitality concerns the basic internal mechanics of union representation: the presence and density of a network of union delegates or stewards or representatives in the workplace; the existence and regularity of mechanisms and procedures that ensure links to members and to particular groups of members (for example, identity structures); the existence and relative effectiveness of different means of communication between members, stewards and local leaders and with other levels of the union; and the existence of policies and programmes to integrate new groups and new activists. A wide variety of studies, including our own research observations, suggest that the basic mechanics of deliberative vitality are critical to internal union solidarity (Bourque and Rioux, 2001;Peetz and Pocock, 2009). The second aspect of deliberative vitality concerns the extent of membership participation and the quality of engagement in these different deliberative structures.…”
Section: Infrastructural Resourcesmentioning
confidence: 97%
“…The decline in the power and influence of trade unions in developed economies has been widely acknowledged in the academic literature (Frege and Kelly 2003;Heery, Kelly and Waddington 2003;Johnson and Jarley 2004;de Turberville 2007;Cooper and Ellem 2008;Peetz and Pocock 2009;Heery 2011). For example, union density in Australia has declined sharply in the 1990s falling from 41% in 1990s to 25% in 2000, and while there have been some periods and areas of growth, overall union density in 2010 was down to 18% (Cooper and Ellem 2011).…”
Section: Trade Union Renewal and Revitalizationmentioning
confidence: 96%
“…The focus of this literature has been on discovering new strategies and mechanisms to address these problems, specifically in developing new power resources that can be exercised to halt and perhaps reverse the decline The International Journal of Human Resource Management 2511 in union influence. Two broad strategies can be noted (Heery 2011): developing collective worker identity and action, including exploring different approaches to the recruitment of new union members, servicing existing members and restructuring trade unions; and developing coalitions, or forms of 'external solidarity' (Lévesque and Murray 2006) with other civil society organizations and social movements, to mobilize a broader network of opposition (Frege and Kelly 2003;Heery et al 2003;Badigannavar and Kelly 2005;Peetz and Pocock 2009). In addition to these two dominant approaches, there are those who argue for a revitalized focus on political action for trade unions (Delaney 1991;Marsh 1992;Heery 1998;Hurd, Milkman and Turner 2003;Hamann and Kelly 2004;Wilson and Spies-Butcher 2011).…”
Section: Trade Union Renewal and Revitalizationmentioning
confidence: 99%